In Praise of the Guilty Project: A Criminal Defense Lawyer's Growing Anxiety About Innocence Projects - Smith, Abbe (2010)
There is nothing more compelling than a story about an innocent person wrongly convicted and ultimately vindicated. An ordinary citizen is caught up in the criminal justice system through circumstances beyond his or her control, spends many years in prison, and then one day, with the assistance of a dedicated lawyer, is freed. Often, when DNA is behind a vindication, not only is the innocent person exonerated but the true perpetrator is identified. This is a significant achievement even though it can also lead apologists for the system—even police and prosecutors implicated in the wrongful conviction—to proudly declare that the system “worked.” The work of lawyers, journalists, and others involved in the “innocence movement”— or, as one participant has called it, the “innocence revolution,”—has been justly lauded. In the relatively few years since prisoners began to be freed because of post-conviction DNA testing, advocates for the innocent have accomplished “breath-taking . . . results.” They have ushered in “an exciting new period of American criminal justice,” a “transformation,” that is truly “groundbreaking.” Some have proclaimed the innocence movement “a new civil rights movement” of the twenty-first century. Because of the publicity attending exonerations, the narrative of innocence—with its tales of bungled or corrupt police work, mistaken or bought witnesses, coerced or false confessions, unethical or incompetent lawyers, and phony science—has caught fire, leading to important legislative changes and some new police practices. Most importantly, the narrative may be trickling down to jurors. Armed with these stories, jurors might view questionable evidence with greater skepticism, and in so doing, ensure that the prosecution meets its burden of proof. Given all this—the draw of innocence, the importance of vindicating innocence, the fact that innocence advocacy may have helped level the criminal justice playing field, the goodness of defending the innocent—how can a criminal defense lawyer have the audacity, the nerve to complain? Why can’t Innocence Projects and “Guilty Projects”—the traditional law school criminal defense clinic—coexist in peace, each making an important contribution? What possible concerns could be raised that are not rooted in envy? In this essay the author discusses three growing concerns about Innocence Projects: first, the tendency toward innocence “one-upmanship” or arrogance; second, the focus on innocence—especially DNA-proven innocence—as the chief currency in criminal justice reform; and third, the popularity and increasing ascendancy of Innocence Projects at law schools